Surgery performed at night by continuously working surgeons contributes to a higher incidence of intraoperative complications in video-assisted thoracoscopic pulmonary resection: a large monocentric retrospective study. (20th September 2019) - Chen, Chunji; Zhang, Xiaofeng; Gu, Chang; Wang, Yiyang; Liu, Kun; Pan, Xufeng; Fu, Shijie; Fan, Limin; Wang, Rui
Abstract: : OBJECTIVES: Our goal was to assess the influence of working hours and working at night on intraoperative complications on surgeons conducting video-assisted pulmonary resections. METHODS: We identified all patients who underwent video-assisted thoracoscopic surgery (VATS) in Shanghai Chest Hospital from January 2015 to April 2017. Univariable and multivariable logistic analyses were used to analyse independent risk factors for intraoperative complications. A 1:4 propensity score matching analysis was conducted to verify those results. RESULTS: A total of 15 767 patients who underwent VATS pulmonary resection were included in this study. Among them, 15 280 patients (96.1%) were operated on during daytime working hours and 487 (3.1%) at night. A total of 203 (1.3%) intraoperative complications occurred. Vascular injury was the main cause of intraoperative complications, accounting for 92.1% (187/203). Multivariable logistic regression indicated that age [odds ratio (OR) = 1.68, 95% confidence interval (CI) 1.43–1.98; P  < 0.001], gender (OR = 1.71, 95% CI 1.26–2.32; P  = 0.001), surgical experience (OR = 2.07, 95% CI 1.56–2.75; P  < 0.001), type of surgery (OR = 0.31, 95% CI 0.20–0.49; P  < 0.001) and operative periods (OR = 2.69, 95% CI 1.61–4.86; P  < 0.001) were independent predictors for intraoperative complications. The incidence of intraoperative complications during night-time surgery was significantly higher than that during daytime working hours. A 1:4 propensity score matching-based results verification showed that night-time surgery was still an independent risk factor after propensity score matching (OR = 2.76, 95% CI 1.47–5.15; P  = 0.002). CONCLUSIONS: The incidence of intraoperative complications from VATS pulmonary resection performed during night hours was significantly higher than that performed during working hours. In the present labour environment, thoracic surgeons should avoid night-time surgery whenever possible.